If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8x + 1) = 24x Reorder the terms: 3(1 + 8x) = 24x (1 * 3 + 8x * 3) = 24x (3 + 24x) = 24x Add '-24x' to each side of the equation. 3 + 24x + -24x = 24x + -24x Combine like terms: 24x + -24x = 0 3 + 0 = 24x + -24x 3 = 24x + -24x Combine like terms: 24x + -24x = 0 3 = 0 Solving 3 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9b-7=5b+5 | | 7*x+51=0 | | 3s(6t^4-2s^2-3t-6)= | | 2ln(x+4)=-2 | | 7*x+51=72 | | -1.3333333333333333(33+m)=12+m | | (4x-4)*(2x+7)= | | 7*x+51=96 | | 2k-7= | | 9+(4/x)=7 | | 7x+34= | | x^2+y^2-12x-12y+36=0 | | 25u+73=19u+109 | | 2x^2+13x=27 | | 9x+5y=14 | | f(x)=-9x+6 | | 4n-4=7n+17 | | x+15=130 | | log[3](-4x)=14 | | 2n-5=4n+7 | | z-10=19-19z | | x-30=80 | | 8(-19x+5)=-96-16x | | (6y+6)-(3+5y)=6 | | 49y+97=49y-29 | | 5/-3=18 | | 36x^2+63x= | | .11x+.12(3x)=188 | | a^4/a^2 | | (9x^2+3x+4)-(7x+3)= | | 3x-2y=7x-5 | | -4/7(-5) |